Impact of indoor Air Pollution on the Linear growth of children in Jimma, Ethiopia - Elias Mulat; Dessalegn Tamiru; Kalkidan Hassen Abate (BMC, 2024)
Abstract Background Stunting in children is the term for reduced linear growth and development, which is frequently brought on by a persistently inadequate diet, recurrent infections and chronic diseases or poor health conditions. Apart from the classic covariates of stunting, which include diet and illness, the relative contribution of household air pollution to chronic nutrition conditions is least studied. Hence, this study is conducted to investigate the impact of household air pollution on the linear growth of under-five children in Jimma town, Ethiopia. Methods A prospective cohort study was employed to collect data from 280 under-five children who lived in households using solid fuel (exposed group, n = 140) and clean fuel (unexposed group, n = 140). Height-for-age Z scores were compared in both groups over a 12-month follow-up period. The difference in differences estimators were used for comparison of changes in the height-for-age Z scores from baseline to end line in exposed and non-exposed groups. The independent effect of the use of solid fuels on height-for-age Z scores was analyzed through a multivariable linear regression model. Statistical Significances were declared at P < 0.05 and 95% CI level. Results In an unadjusted model (Model 1), compared with the clean fuel type, the mean difference in the height-for-age Z score of children in households using solid fuel was lower by 0.54 (-0.54, 95% CI -0.97, -0.12, P = 0.011). The beta coefficient remained negative after adjusting for age and sex (Model 2 -0.543, 95% CI -1.373, -0.563) and sociodemographic variables (Model 3: -0.543, 95% CI -1.362, -0.575). In the final model (Model 4), which adjusted for wealth quantile, dietary practice, water, sanitation and hygiene status and household food insecurity access scale, the beta coefficient held the same and significant (beta: -0.543, 95% CI -1.357, -0.579, P < 0.001). Higher HAZ scores were observed among female child (β: = 0.48, 95%CI: 0.28, 0.69), Child with father attended higher education (β: = 0.304 95%CI: 0.304, 95% CI 0.19, 0.41) as compared to male gender and those who did not attend a formal education, respectively. In contrast, child living in households with poor hygiene practices had lower HAZ score (β: -0.226, 95% CI: -0.449, -0.003), P < 0.001. Conclusions Exposure to indoor air pollution was inversely related to linear growth. Furthermore, sex, educational status and hygiene were found relevant predictors of linear growth. In such a setting, there is a need to step up efforts to design and implement public education campaigns regarding the health risks associated with exposure to household air pollution. Promoting improvements to kitchen ventilation and the use of improved cooking stoves, which will help to mitigate the detrimental effects of indoor air pollution on child growth impairment and its long-term effects.